1969
DOI: 10.1111/j.1476-5381.1969.tb09543.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of suxamethonium by different types of plasma

Abstract: 1. A method, based on the use of the isolated frog rectus aibdominis preparation, is described for studying quantitatively the hydrolysis of suxamethonium at low concentrations. 2. Rates of hydrolysis of butyrylcholine, 10 mm, benzoylcholine, 0.05 mm, and suxamethonium, 0025 mM, by plasma from different species and human plasma with genetic variants of cholinesterase were measured. 3. The rates of hydrolysis of suxamethonium by different types of plasma vary widely. Human plasma with usual cholinesterase and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1969
1969
2003
2003

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
(19 reference statements)
0
23
0
Order By: Relevance
“…IC 50 values were calculated by logarithmic plot analysis. Inhibition coefficient values (K i ) were calculated from the equation K i ϭ IC 50 /1 ϩ (S/K m ), as described by Hobbiger and Peck (1969) where S represents the concentration of acetylthiocholine (0.75 mM), and K m represents the Michaelis-Menten constant.…”
Section: Methodsmentioning
confidence: 99%
“…IC 50 values were calculated by logarithmic plot analysis. Inhibition coefficient values (K i ) were calculated from the equation K i ϭ IC 50 /1 ϩ (S/K m ), as described by Hobbiger and Peck (1969) where S represents the concentration of acetylthiocholine (0.75 mM), and K m represents the Michaelis-Menten constant.…”
Section: Methodsmentioning
confidence: 99%
“…For example, some bisquaternary compounds, which are more potent inhibitors ofAcChoEase than their monoquaternary counterparts, bind poorly to BtChoEase (6). Human BtChoEase (h-BtChoEase) is of interest to anesthesiologists and geneticists because it is responsible for breakdown ofthe short-term muscle relaxant succinylcholine (7) and because numerous genetic variants exist in which the rate of succinylcholine hydrolysis is reduced (8).…”
mentioning
confidence: 99%
“…Hobbiger & Peck (1969) have shown that the plasma cholinesterase of different species hydrolyses representative substrates at varying rates, the order for suxamethonium being monkey>man> rat>dog>cat. Other substrates were generally hydrolysed faster by man than by the latter species.…”
Section: Discussionmentioning
confidence: 99%